GENDER DIFFERENCES IN PHYSICAL ACTIVITY AMONG THE UNIVERSITY STUDENTS IN THE VISEGRAD (V4) COUNTRIES - Pongrác ÁCS; Józef BERGIER; Ferdinand SALONNA; Jan JUNGER; Monika GYURO; Ágnes SIMON-UGRON; Zsanett WELKER; Alexandra MAKAI (Cluj University Press, 2017)
Introduction. Sedentary way of life has become a global phenomenon in the past decades. Therefore, the number of people with excess weight has doubled in the past 30 years. Besides this fact, it has been justified that more than half of the population is overweight. Even young adults are affected by the problem. It is an important issue because 60% of the overweight young people keep their excess body weight in later adulthood increasing the risk of different diseases. Material and method. Our study aims at assessing the differences between the health status and the physical activity among young people (secondary school and university students) in the Visegrad (V4) countries. Our current research examines the differences in the physical activity among university students regarding their sexes (n=2237). SPSS 22.00 software was used for statistical analysis. Results. According to the results, we found significant differences (p<0.001) both in the extent of physical activity values, except for moderate activities between sexes. Significant differences were observed between the countries concerning the examined parameters (p<0.001). Among Polish university students, we found significant differences in sexes in the total, vigorous, moderate and walking MET/week values (p<0.05).Almost identical results were found in the Czech Republic and the other V4 countries compared to Poland. There were no significant gender differences in the rate of walking activities regarding the Czech respondents (p=0.426).The results of the Hungarian respondents approximated those of the Slovak ones; no differences were found in the physical activity category of the vigorous and moderate activity values (p>0.05). In Slovakia, we found significant differences between sexes in total MET/week and walking activities (MET/week) (p<0.001), thus, female students were found to be more active than males caused by the higher rates of walking activities of women. Conclusion. The V4 countries are not in an advantageous situation concerning physical activity in the European framework because only 21-35% of the population does sports once a week. According to our results, university students show a more positive picture on physical activity than the adult population. However, there are some specific risk groups. 43.8% of female and 57.3% male students can be considered as persons with high physical activity. Our findings may play a major role in the development of intervention programs targeting young people and in the concern of the differences between sexes. Furthermore, these results may call young people's attention to health maintenance to preserve their fitness for getting better activity figures.